Segregação socioespacial nas cidades siderúrgicas: Ouro Branco/MG - Bruna Hamacek Vianna (2018)
The city of Ouro Branco became part of the Brazilian industrialization period of the 70s with the construction of the state-owned steel plant Açominas. This lead to the expansion of the existing city, of colonial origins and limited infrastructure, which was planned to house a population of 180 thousand inhabitants once the maximum production capacity was reached. The urban plan was developed by the João Pinheiro Foundation, which divided the city into four zones: urban, industrial, agricultural and preservation. The housing division in the urban zone neighborhoods was done according to the position of the workers, allowing different access to the urban equipment, to the residential types and to the environmental quality for each sector, resulting in a planned social and spatial segregation. During the construction of the project, several budget cuts took place as a consequence of the economic crisis suffered by the country, reflecting in the city, in which only the first phase of the housing planning was consolidated. This work uses literature review, mapping development, and field work to understand whether the city continues to be segregated after 40 years of its expansion plan. As it will be later revealed, via the spatial and social analysis of the city throughout its development, the social division continues to take place, due to governmental actions and due to the real state, even after the steel plant refrained from the urban questions regarding the city.